Impact of Uric Acid Levels on Kidney Graft Function - Yakupoglu, U.; Berber, I.; Gurluler, E.; Gures, N.; Cakiroglu, A.; Gurkan, A. (WILEY-BLACKWELL, 2012)
American Transplant Congress, Boston, MA, MAY, 2012